2005
DOI: 10.1128/iai.73.8.4941-4947.2005
|View full text |Cite
|
Sign up to set email alerts
|

Phagocyte-Derived Reactive Oxygen Species Do Not Influence the Progression of Murine Blood-Stage Malaria Infections

Abstract: Phagocyte-derived reactive oxygen species have been implicated in the clearance of malaria infections. We investigated the progression of five different strains of murine malaria in gp91 phox؊/؊ mice, which lack a functional NADPH oxidase and thus the ability to produce phagocyte-derived reactive oxygen species. We found that the absence of functional NADPH oxidase in the gene knockout mice had no effect on the parasitemia or total parasite burden in mice infected with either resolving (Plasmodium yoelii and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 64 publications
0
30
1
Order By: Relevance
“…Based on the observation that NAD(P)H gp91 phox -deficient mice can develop cerebral malaria, it has been suggested that ROS are probably not involved in its pathogenesis [86]. Our interpretation is somehow different.…”
Section: Mechanism Underlying the Protective Effects Of Co: Inhibitiocontrasting
confidence: 46%
“…Based on the observation that NAD(P)H gp91 phox -deficient mice can develop cerebral malaria, it has been suggested that ROS are probably not involved in its pathogenesis [86]. Our interpretation is somehow different.…”
Section: Mechanism Underlying the Protective Effects Of Co: Inhibitiocontrasting
confidence: 46%
“…Rather, our data suggest that P. yoelii-infected red blood cells can directly activate macrophages to carry out their effector functions and that these activated macrophages then mediate direct antiparasitic effects. The mechanisms by which macrophages kill or cripple blood-stage parasites are somewhat unclear; despite several studies reporting a role for reactive oxygen intermediates in parasite killing (7,8,9,11), this respiratory burst does not seem to be essential, since gp91 phoxϪ/Ϫ mice lacking the NADPH oxidase system are no more susceptible to P. yoelii, P. chabaudi, or P. berghei infections than wild-type mice are (39).…”
Section: Discussionmentioning
confidence: 98%
“…The reactive oxygen species released by leucocytes play a major role in the immune response against Plasmodium parasites and have been associated with efficient parasite clearance [66 -68]. Nevertheless, the exact mechanisms involved are controversial [69,70] and the release of reactive oxygen species in the circulation may on some occasions have more pathological than beneficial effects [29,71].…”
Section: (C) Prevalence and Parasitaemiamentioning
confidence: 99%